Pulmonary platelet aggregates: possible cause of sudden peroperative death in adults undergoing liver transplantation. Issue 3 (March 1993) - Sankey, E A; Crow, J; Mallett, S V; Alcock, R J; More, L; Burroughs, A K; Rolles, K
Abstract : AIMS: To determine if massive pulmonary platelet thromboembolism is a common cause of peroperative death following liver transplantation; and to compare the incidence of this event with patients dying after non-transplantation procedures. METHODS: Necropsy tissues from all patients dying within 10 days of operation during the past three and a half years were studied (six liver transplantations and 13 unrelated operations). Haematoxylin and eosin stained sections of all tissues were examined. Additional sections of lung tissue were immunostained for constituents of thrombus (fibrin and platelets). RESULTS: At necropsy the lungs from all six liver transplant recipients were heavy with a rubbery texture and little oedema fluid. Those from non-transplantation patients appeared normal or very oedematous. Microscopic examination showed that there were numerous platelet aggregates occluding pulmonary capillaries in all six transplant recipients, but in only three of the non-transplant patients. These thrombi were numerous in patients dying during surgery and the number was underestimated in routine sections because of the surrounding capillary congestion. Detection was improved by immunostaining for platelets with factor XIIIA and platelet glyco-protein IIIa. CONCLUSIONS: Massive platelet thromboembolism is a likely cause of death in patients dying unexpectedly following recent liver transplantation. Non-transplantation patients dying during surgery who show similar appearances usually have conditions known to have a high risk of thrombosis or embolism (cement hypotension syndrome and disseminated intravascular coagulation). The cause of this extensive platelet activation in liver transplant recipients is uncertain and may be multifactorial. The unusual rubbery consistency of the lungs on macroscopic examination could alert the pathologist to the underlying condition. Immunostaining for platelets improves the detection microscopically.